Analysis of Tax Planning for Corporate Income Tax Case Study at PT.Victoria Care Indonesia Year 2022 - Kharisma Endarty; Ida Farida Adi Prawira (Jurnal Riset Perpajakan: Amnesty, 2024)
The purpose of this study is to delve into the tax planning strategies employed by PT Victoria Care Indonesia, aimed at optimizing the company's tax liabilities. Tax planning is a crucial aspect of corporate finance, allowing businesses to strategically manage their tax obligations within the bounds of the law. Through meticulous planning and analysis, companies can identify opportunities to minimize tax burdens while remaining compliant with regulatory requirements. In this research, secondary data is utilized, drawing from various sources within PT Victoria Care Indonesia. The quantitative approach adopted facilitates a systematic examination of the company's tax planning practices. By employing descriptive analysis methods, the study provides a comprehensive overview of the tax planning landscape within the organization. The findings reveal significant efficiencies derived from the implementation of tax planning measures. Specifically, two key areas emerge as focal points of tax optimization: investment in human capital through training and development initiatives, and the provision of health benefits to employees in monetary form. These strategies not only contribute to enhancing employee welfare but also serve as effective tax planning tools, enabling the company to capitalize on tax incentives and deductions associated with such expenditures. Moreover, the study underscores the importance of integrating tax planning into broader corporate strategies, emphasizing its role as a proactive financial management tool rather than a reactive compliance exercise. By aligning tax planning efforts with organizational goals, PT Victoria Care Indonesia can not only minimize tax liabilities but also drive sustainable growth and profitability. In essence, this study sheds light on the nuanced complexities of tax planning within the context of corporate governance, underscoring its significance in optimizing financial performance and ensuring long-term viability for businesses operating in an increasingly intricate regulatory environment.